Longissimus Dorsi Muscle Transcriptomic Analysis of Simmental and Chinese Native Cattle Differing in Meat Quality - Meng, Xiangren; Gao, Ziwu; Liang, Yusheng; Zhang, Chenglong; Chen, Zhi; Mao, Yongjiang; Huang, Bizhi; Kui, Kaixing; Yang, Zhangping (Frontiers in Veterinary Science, 2020)
With the rapid development of economy, the demand for beef, in regards to quantity and quality, by consumers has been increasing in China. Chinese native cattle are characterized by their abundant genetic resources, unique origins, large breeding stocks and robust environmental adaptability. Thus, to explore genetic mechanisms on regulating meat quality in Chinese native cattle is of great importance to satisfy increased requirements for beef production. In this study, we investigated 3 breeds including Yunling, Wenshan and Simmental cattle at the age of 12 months. Animals were classified into 3 groups (n=5/breed). Growth traits including body weight and body size, and plasma hormone levels were measured. Body weight of Wenshan cattle was significantly lower than that of Yunling and Simmental cattle (P < 0.05). Again, body size indexes, such as withers height, body slanting length, chest circumference, hip and rump length, were significantly lower in Wenshan cattle than that of Yunling and Simmental cattle (P < 0.05). However, there were no significant differences in those indexes between Yunling and Simmental cattle (P > 0.05). Cattle were slaughtered at the age of 18 months and then meat color, pH, pressing losses, muscle tenderness and cooking losses were measured at 0, 1, 2, 3, 5 and 7 days. Data revealed the differences in meat quality among the 3 breeds analyzed. Based on transcriptomic sequencing and bioinformatic analysis, we observed 3198 differentially expressed genes related to meat quality, of which 1750 genes were upregulated. Moreover, we found 2 important signaling pathways closely linked to meat quality, including adipocytokine signaling pathway (e.g., leptin, LEPR) and protein processing in the endoplasmic reticulum (e.g., STAT3, HSPA12A, and CAPN1). The results of transcripts were further verified by qRT-PCR. Using correlation analysis between gene expression levels and shear force, we also identified 2 functional genes (e.g., HSPA12A and CAPN1) associated with meat quality. Overall, this study provides new sights into novel targets and underlying mechanisms to modulate meat quality in Chinese native cattle.